Discourse structure and diversity of the references in a Selected texts - Miro, Rafeq S.; Othman, Nawzet A.; Abdelkrim, Abdulqadir N. (Humanities Journal of University of Zakho, 2019)
Structurally, the text depends on complex and effective linguistic and semantic structures. In the past, comparative studies uncovered the contents of the text leaving the artistic side, but with the transmission of the structural ideas to both comparative and literary fields, it become clear that the text or the statement can be analyzed in isolation from the social and historical environment. Thus, emerged the theory of immanence by Hilmsliff and before him the theory of Semiosis by Charles Sanders Peirce. According to their theories , the sign indicates another sign and then the sign indicated by the first indicates to the third and so indications continue on this way provided that they are consistent with the content of the statement,This research is an attempt to show the extent to which these terms overlap with the texts of the discourse and their inconsistency with those texts, because they contain guidance towards the abstraction of the particles and the approach to the totality with the dimensions of the relationship between the text and its constituent environment and thus a presence parallel to the real existence of the statement in particles. In this context, the research will attempt to find the relationship between the text and its comparative reference contexts, because it takes into consideration the orientation of the recipient, which in turn is an engine for understanding the references of the text. Thus this study concluded with this results.